Application Of Autonomous Maintenance To Reduce Failure Rate Of Bearings In Food Production Line A Case Study - Hanafiah, Amir Hamzah M. (Universiti Sains Malaysia, 2019)
The current manufacturing industries are blooming in the whole world where it can be said that every country mostly depend on this industry to generate economy. As in this modern world, industries are competing between each other. To ensure the company is performing well, one of the most important factors is the company can meet all the customer demand. To make this happen, the production of the company should in a smooth condition without any breakdown occurred. In this case, maintenance play a very significant role to fulfill the company desire. In this project, a single pillar of Total Productive Maintenance (TPM) is being study on its significant improvement that it can make. The pillar is the Autonomous Maintenance (AM) where AM is the pillar for the operators to do maintaining task in order to keep machine sustainability. This project is a case study done at a food manufacturing company at Enstek, Negeri Sembilan. The case study is about the application of Autonomous Maintenance to reduce machine downtime caused by bearing failure. The outcome from this case study is a lubrication system that improved the bearing failure rate at the production line.